Carbon isotope discrimination in leaves of the common paperbark tree, Melaleuca quinquenervia, as a tool for quantifying past tropical and subtropical rainfall - Tibby, John; Barr, Cameron; McInerney, Francesca A.; Henderson, Andrew C.G.; Leng, Melanie J.; Greenway, Margaret; Marshall, Jonathan C.; McGregor, Glenn B.; Tyler, Jonathan J.; McNeil, Vivienne (Wiley, 2016)
Quantitative reconstructions of terrestrial climate are highly sought after but rare, particularly in Australia. Carbon isotope discrimination in plant leaves (Δleaf) is an established indicator of past hydroclimate because the fractionation of carbon isotopes during photosynthesis is strongly influenced by water stress. Leaves of the evergreen tree Melaleuca quinquenervia have been recovered from the sediments of some perched lakes on North Stradbroke and Fraser Islands, south-east Queensland, eastern Australia. Here, we examine the potential for using M. quinquenervia ∆leaf as a tracer of past rainfall by analysing carbon isotope ratios (δ13C) of modern leaves. We firstly assess Δleaf variation at the leaf and stand scale and find no systematic pattern within leaves or between leaves due to their position on the tree. We then examine the relationships between climate and Δleaf for an 11 year timeseries of leaves collected in a litter tray. M. quinquenervia retains its leaves for 1-4 years; thus cumulative average climate data are used. There is a significant relationship between annual mean ∆leaf and mean annual rainfall of the hydrological year for 1-4 years (i.e. 365-1460 days) prior to leaf fall (r2=0.64, p=0.003, n=11). This relationship is marginally improved by accounting for the effect of pCO2 on discrimination (r2=0.67, p=0.002, n=11). The correlation between rainfall and Δleaf, and the natural distribution of Melaleuca quinquenervia around wetlands of eastern Australia, Papua New Guinea and New Caledonia offers significant potential to infer past rainfall on a wide range of spatial and temporal scales.